Comparison of application of Fenton, Intergrowth-21st and WHO growth charts in a population of Polish newborns - Dominik Jakubowski; Daria Salloum; Marek Maciejewski; Magdalena Bednarek-Jędrzejek; Anna Kajdy; Aneta Cymbaluk-Płoska; Ewa Kwiatkowska; Andrzej Torbé; Sebastian Kwiatkowski (IMR Press, 2021)
Background: Growth charts are the primary tools for evaluating neonatal birth weight and length. They help and qualify the neonates as Appropriate for Gestational Age (AGA), Small for Gestational Age (SGA), or Large for Gestational Age (LGA). The most commonly used neonatal charts include Intergrowth-21st, WHO, and Fenton. The aim of the study was to compare the tools used for assessing neonatal birth weight and the incidence of SGA and LGA using the different charts. Methods: Data on 8608 births in the Clinical Department of Obstetrics and Gynecology were compared. We divided the patient population into five gestational age groups. The 10th and 90th percentiles were calculated. The percentage of cases meeting the SGA and LGA criteria was determined. Results: Statistically significant differences between growth charts were identified for each of the groups. The 10th percentile for the study population corresponded to 2970 g for females and 3060 g for males born in the 40th week of gestation. The 90th percentile values were 4030 g and 4120 g. Our analysis showed a statistically significant difference in detection of LGA or SGA between three growth charts and our data both in male (χ2(3) = 157.192, p < 0.001, Kramer's V = 0.444) and female newborns (χ2(3) = 162.660, p < 0.001, Kramer's V = 0.464). Discussion: Our results confirm that differences exist between growth charts. There is a need for harmonizing growth assessment standards. It is recommended that a growth chart should be developed for the Polish population, which would improve the diagnosis of SGA and LGA.